2020
DOI: 10.3390/life10120327
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electronic Health Record Implementation and Barriers to Adoption and Use: A Scoping Review and Qualitative Analysis of the Content

Abstract: Despite the great advances in the field of electronic health records (EHRs) over the past 25 years, implementation and adoption challenges persist, and the benefits realized remain below expectations. This scoping review aimed to present current knowledge about the effects of EHR implementation and the barriers to EHR adoption and use. A literature search was conducted in PubMed, Web of Science, IEEE Xplore Digital Library and ACM Digital Library for studies published between January 2005 and May 2020. In tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
96
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(106 citation statements)
references
References 144 publications
(452 reference statements)
7
96
0
3
Order By: Relevance
“…39 Most physicians in our study indicated that technical support is usually available and that this support is effective. While technical support has been previously identified as a barrier to EHR adoption and use, 40 this did not appear to be a key concern in our sample. Clinical support is less readily available, with a minority of physicians responding that they "always" or "often" received assistance with EHR inbox tasks, while many physician respondents found additional staff support with EHR tasks and documentation to be a useful practice-level strategy.…”
Section: Discussionmentioning
confidence: 61%
“…39 Most physicians in our study indicated that technical support is usually available and that this support is effective. While technical support has been previously identified as a barrier to EHR adoption and use, 40 this did not appear to be a key concern in our sample. Clinical support is less readily available, with a minority of physicians responding that they "always" or "often" received assistance with EHR inbox tasks, while many physician respondents found additional staff support with EHR tasks and documentation to be a useful practice-level strategy.…”
Section: Discussionmentioning
confidence: 61%
“…To provide an overview of available knowledge on the implementation and use of electronic health record (EHR) systems, including tethered personal health records (PHRs), the article by Tsai et al [ 3 ] presents the current knowledge on the effects of EHR implementation and the barriers to EHR adoption and use. The authors identified positive as well as negative effects on the clinical work, data and information, patient care and economic impact.…”
Section: Presentation Of the Papersmentioning
confidence: 99%
“…[9][10][11] Patient engagement has received considerable attention in recent years, 10 and patient portals may contribute to engaging the patients actively in their care by granting them access to their health data and providing additional functionalities. 7,[12][13][14] To date, we find a very heterogeneous landscape and a broad diversity of patient portals 15 regarding their intended deployment and functionalities. 8,16 Patient portals can be projected for specific care sectors, for example, primary or secondary care based on each care sector's different needs.…”
Section: Introductionmentioning
confidence: 99%
“…A PHR or personal health record provides patients with web-based access to their health data that is under the control of the patient, 1 while an EHR typically is under the control of the provider. 5,9,14 Scheplitz et al 20 created a framework for patient portal functionalities to record all possible functions to identify specification gaps related to software development. Walker et al developed a framework to evaluate how well health information technology can support patient engagement by applying five engagement scoring levels.…”
Section: Introductionmentioning
confidence: 99%